DETERMINAN PROBABILITY OF DEFAULT DALAM PERHITUNGAN EXPECTED CREDIT LOSS PERBANKAN - Hartanto, Ary Daniel; Setijaningsih, Herlin Tundjung (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This study aims to analyze the influence of the credit risk profile, credit growth target and the macro economy (GDP, exchange rate and inflation) on the probability of default in generating expected credit loss as stipulated in PSAK 71. The research was conducted at PT Bank X during the 2016-2020 observation using multiple linear regression analysis. The results of this study state that the credit risk profile, credit growth target and the exchange rate have a positive and significant effect on the probability of default (PD), while GDP and inflation have a significant negative effect on PD. The research results imply that the implementation of good credit risk management is expected to reduce the rate of default which can be caused by the credit growth target and macroeconomic conditions, especially GDP and exchange rates which have a significant effect on defaults which will ultimately affect the formation of expected credit loss (ECL) in the financial statements.